2015
DOI: 10.1093/cid/ciu957
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobials Increase Travelers' Risk of Colonization by Extended-Spectrum Betalactamase-Producing Enterobacteriaceae

Abstract: Colonized travelers contribute to the pandemic spread of resistant intestinal bacteria. This study is the first to show that antimicrobial use during travel predisposes to colonization by intestinal extended-spectrum beta-lactamase-producing Enterobacteriaceae. Travelers refrain from taking unnecessary antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
239
2
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(264 citation statements)
references
References 32 publications
16
239
2
7
Order By: Relevance
“…The most prominent increases were observed in less abundant genes encoding resistance to sulfonamide (2.6-fold), trimethoprim (7.7-fold), and beta-lactams (2.6-fold). The metagenomic results offer a new and broadened perspective on the changes of the antibiotic resistance potential of the human gut microbiome after travel, providing an independent complement to previous studies targeting a limited number of bacterial species or antibiotic resistance genes (11,(13)(14)(15)(16)(17)21).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The most prominent increases were observed in less abundant genes encoding resistance to sulfonamide (2.6-fold), trimethoprim (7.7-fold), and beta-lactams (2.6-fold). The metagenomic results offer a new and broadened perspective on the changes of the antibiotic resistance potential of the human gut microbiome after travel, providing an independent complement to previous studies targeting a limited number of bacterial species or antibiotic resistance genes (11,(13)(14)(15)(16)(17)21).…”
Section: Discussionmentioning
confidence: 94%
“…In recent years, acquisition of Enterobacteriaceae strains resistant to cephalosporin antibiotics by production of extendedspectrum beta-lactamases (ESBLs) have been quantified in travelers from the Netherlands (9, 10), France (11), Australia (12), Sweden (13)(14)(15), Germany (16), and Finland (17). Certain risk factors, such as intake of antibiotics and a travel destination on the Indian peninsula, appear to increase the risk of acquisition (9,10,(12)(13)(14)(15)17). Consequently, there is general concern over the contribution of travel to the global dispersal of antibiotic-resistant bacteria.…”
mentioning
confidence: 99%
“…[13][14][15] In a study from Finland, traveller's diarrhea (adjusted OR 31.0, 95% CI 2.7-358.1) and antibiotic therapy for traveller's diarrhea (adjusted OR 3.0, 95% CI 1.4-6.7) were the most important risk factors for acquiring ESBLproducing E. coli. 16 The same author group showed that use of loperamide alone to treat mild traveller's diarrhea was not associated with an increased risk of colonization with ESBLproducing E. coli. 17 The largest and most comprehensive travel study investigating multidrug-resistant E. coli colonization among returning travellers was performed in the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…Overcrowded conditions, especially during the Hajj, are a major risk for dissemination of antibiotic resistance (AR) bacteria. Moreover, taking antibiotics during travel may play a major role in selecting AR bacteria (8). However, without colistin selection in pilgrims during the Hajj, mcr-1-resistant strains can disseminate among pilgrims, demonstrating a low transmission fitness cost.…”
mentioning
confidence: 99%